La «señal» del pedrero Obra y fábrica del claustro de la catedral de Toledo (1383-1485) - Yuste Galán, Amalia María (Bibliothèque de la Casa de Velázquez, 2022)
The construction of the cloister of Toledo Cathedral took place between the 14th and 15th centuries. The comparison of the accounting documentation it generated with the monument itself and the lapidary signs identified thanks to the application of new technologies, has made it possible to approach the daily life of one of the most important construction undertakings of the Castilian Middle Ages and to contribute to a new reading of the resources, the people and the organization of the stonemasonry workshops.